(untitled) (Research, Society and Development, 2025)
Introduction: Adult-onset Still’s disease (AOSD) is a rare systemic autoinflammatory disorder of unknown etiology that, when it occurs during pregnancy, poses a clinical challenge due to the risk of obstetric and systemic complications. Objective: To describe the clinical course, diagnostic approach, and multidisciplinary management of a pregnant woman with AJS, highlighting the maternal and perinatal implications. Methodology: A qualitative, descriptive, single-case report study was conducted with retrospective analysis of the electronic medical record following the CARE guidelines, ensuring confidentiality and informed consent. Discussion: SLE in pregnancy poses diagnostic challenges due to its similarity to serious obstetric conditions. in this case, the patient with a history of systemic inflammatory disease and autoimmune hemolytic anemia progressed favorably under specialized management and multidisciplinary follow-up, which allowed close monitoring of the mother-fetus pair and a positive neonatal outcome despite preterm delivery and premature rupture of membranes. Conclusion: ESA during pregnancy requires a high index of suspicion, timely diagnosis, and interdisciplinary management; individualized therapy and continuous monitoring are essential to reduce maternal and fetal morbidity and mortality.